1995
DOI: 10.1006/ccog.1995.1001
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory Method for Investigating Influences on Switching Attention to Task-Unrelated Imagery and Thought

Abstract: Thought-intrusions, automatic inferences, and other unintended thought are beginning to play an important role in the study of psychiatric disease as well as normal thought processes. We examine one method for the study of task-unrelated imagery and thought (TUIT). TUIT likelihood was shown to be reliably measured over a wide range of vigilance tasks, to have high short-term and long-term test-retest reliability, and to be sensitive to information processing demands. Likelihood of TUITs was shown to be differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
296
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(331 citation statements)
references
References 0 publications
13
296
0
4
Order By: Relevance
“…Examples include competitive interactions between emotion and cognition (4,39,40), focused attention vs. monitoring of one's environment for behaviorally relevant events (2), and task focus vs. stimulus independent thought (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Examples include competitive interactions between emotion and cognition (4,39,40), focused attention vs. monitoring of one's environment for behaviorally relevant events (2), and task focus vs. stimulus independent thought (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…In a naturalistic study of prospective memory (Ellis, & Nimmo-Smith, 1993) participants were more likely to report having involuntary recollections (i.e., rehearsals) of the to-be-performed intentions when they were not concentrating on the task at hand (see also Sellen, Louie, Harris, & Wilkins, 1997). On the other hand, Giambra (1995) found that the occurrence of TUITs during an ongoing laboratory vigilance task decreased as the frequency of the to-be-detected targets increased.…”
Section: Discussionmentioning
confidence: 99%
“…As the items in all our questionnaires sample routine activities a variety of settings and contexts, receiving a high score implies a rather general trait, which might be taken to suggest a high rate of task-unrelated thought rather than ruminations about the specifics of task performance. It is also possible that such individual differences depend upon endogenous time-linked attention control operators (e.g., Giambra, 1995) and the phenomenological content of the lapses may vary according to context. These sorts of issues could be further explored with awareness probes.…”
Section: Discussionmentioning
confidence: 99%
“…As the managers of Vonnegut's fictional society well knew, lapses of attention are also inherently cognitively debilitating. Indeed, individuals for whom intervals between lapses are very short are typically viewed as impaired (Giambra, 1995). Given the prevalence of attentional failures in everyday life and the ubiquitous and sometimes disastrous consequences of such failures, it is rather surprising that relatively little work has been done to directly measure individual differences in everyday errors arising from propensities for failures of attention.…”
Section: Introductionmentioning
confidence: 99%